PENGARUH AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA, TRANSPARANSI PENGGUNAN DANA DESA, DAN KEBIJAKAN DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT (STUDI KASUS PADA DESA BELULUK, KEC. PANGKALAN BARU, KAB. BANGKA TENGAH) - Yonara, Ririn; Tri Setyo Mulyani, Hendarti; Hasianda Tigor, Ryan (Jurnal Ilmiah Niaga Bisnis Elektronik, 2022)
This study aims to examine the effect of accountability in managing village fund allocations, transparency in the use of village funds, and village fund policies on community welfare. This study also aims to jointly examine the accountability of village fund allocation management, transparency in the use of village funds and village fund policies on community welfare. This research was conducted in the village of Beluluk, Pangkalan Baru District, Central Bangka Regency. This type of research is quantitative research. Types of data used in this study is primary data obtained directly by distributing questionnaires directly to the public Belulu Village. The total population is 3,988 people and the number of samples in In this study, 90 people from the Beluluk Village community as respondents using purposive sampling technique. This study uses the JASP 0.14.1 tool for multiple regression analysis and its analytical methods. Based on the results of data analysis, the results show that Village Fund Allocation Management Accountability has a significant positive effect on Community Welfare. The results of the t-test show that the t count is 2,974 > 1,987 t table with a significance value of 0.004 < 0.05, then H1 is accepted. Transparency in the use of Village Funds has a significant positive effect on Community Welfare. The results of the t-test show that t t-count is 3.207 > 1.987 with a significance value of 0.002 < 0.05, then H2 is accepted. The Village Fund Policy has a significant negative effect on Community Welfare. The results of the t-test show that t count is -2.886 > 1.987 with a significance value of 0.005 < 0.05, then H3 is accepted. This study also shows that accountability for managing village fund allocations, transparency in the use of village funds, and village fund policies together have a significant and significant impact on community welfare. The results of the f test show f count 10,901 > 2,711 f table with a significance value of 0.001 < 0.05, then H4 is accepted.